Ethical Leadership and Employee Performance: A Systematic Literature Review of HRM Perspectives - Anwar, Fahmi Amirulloh (Management Studies and Business Journal (PRODUCTIVITY), 2024)
Ethical leadership plays an important role in influencing employee performance and organizational outcomes. Although much research indicates the positive impact of ethical leadership, there is a gap in understanding of differences in perceptions by generation. This research aims to explore how ethical leadership influences employee performance in various generations using the systematic literature review method and the PRISMA approach. The research results show that ethical leadership not only improves employee performance and job satisfaction, but also improves organizational outcomes by promoting an ethical culture and engagement. The implications of these findings suggest the need to implement ethical leadership tailored to the needs of different generations to maximize employee performance and organizational effectiveness.